Energy recovery analysis through numerical simulations of steam injection in continental shale oil reservoirs - Maryelin Josefina Briceño Montilla; Shouding Li; Zhaobin Zhang; Yanzhi Hu; Jianming He; Zheng Bo; Xiao Li (Journal of Petroleum Exploration and Production Technology)
Abstract In-situ steam injection is a promising method for shale oil extraction from continental reservoirs, addressing China’s growing energy demands. However, optimizing energy utilization to maximize hydrocarbon production remains a significant challenge, particularly in the context of current energy limitations. This study compares two steam injection strategies using a thermal-flow-chemical (TFC) simulator to assess energy recovery efficiency. The first strategy involves continuous steam injection with simultaneous production, while the second introduces a hydrocarbon production phase after injection. Results show that stimulating the production area is critical for achieving high energy recovery ratios in both strategies. Energy recovery is primarily influenced by the interaction between the decomposition front and the reservoir’s thermal and physical properties. Low injection rates with extended periods enhance hydrocarbon generation by approximately 66%, although they require high energy inputs. In contrast, an optimized injection rate in two-phase strategies increases hydrocarbon recovery by up to 90%. Continuous injection prioritizes immediate production but demands higher energy, while two-phase injection focuses on short-term energy accumulation, improving recovery by 30% when injection rate and duration are optimized. Continuous injection risks oversaturating the reservoir, increasing energy losses, and reducing production efficiency. The two-phase strategy, with its favorable fluid distribution and higher remaining energy ratio, offers better potential for sustained production and energy recovery in subsequent treatments. This work introduces an approach to optimizing steam injection strategies from an energy perspective, offering valuable insights for enhancing energy efficiency and resource recovery in shale oil production.